Against and For CBT : Towards a Constructive Dialogue? - House, Richard, 1954-; Loewenthal, Del, 1947- (Ross-on-Wye : PCCS, 2008)
This book offers both a wide range of critical perspectives on the rise and rise of Cognitive Behavioural Therapy (CBT) and substantial responses to them.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Cognitive therapy; Cognitive therapy -- History; Cognitive therapy -- Evaluation